ANALYSIS OF FOOD TABOO CULTURE WITH PROTEIN INTAKE IN PREGNANT WOMEN - Wulandari, Catur; Kardina, Rizki Nurmalya; Wijaya, Satria (Universitas Nahdlatul Ulama Surabaya, 2022)
Food taboos can increase the risk of nutritional deficiencies, especially protein, fat, vitamin A, vitamin E and iron in pregnant women. The purpose of this study was to determine the relationship between food taboo culture and protein intake in pregnant women. This research is an analytic observational study with a cross sectional approach. The sample in this study were all pregnant women in the Pojoksari Village selected by the total sampling method. The results of the study show that most pregnant women practice a food taboo culture. Based on the results of statistical tests with chie square obtained p value = 0.683, which means there is no relationship between food taboo culture and protein intake in pregnant women. Although there is no relationship, it is known that pregnant women who practice food taboo culture have less protein intake to a deficit. Providing education about the food taboo to pregnant women is important to keep their nutritional intake during pregnancy well fulfilled.